Clinical relevance of HLA-DQ eplet mismatch and maintenance immunosuppression with risk of allosensitization after kidney transplant failure - Tran, Jenny; Alrajhi, Ibrahim; Chang, Doris; Sherwood, Karen R.; Keown, Paul; Gill, Jagbir; Kadatz, Matthew; Gill, John; Lan, James H. (Frontiers in Genetics, 2024)
The optimal immunosuppression management in patients with a failed kidney transplant remains uncertain. This study analyzed the association of class II HLA eplet mismatches and maintenance immunosuppression with allosensitization after graft failure in a well characterized cohort of 21 patients who failed a first kidney transplant. A clinically meaningful increase in cPRA in this study was defined as the cPRA that resulted in 50% reduction in the compatible donor pool measured from the time of transplant failure until the time of repeat transplantation, death, or end of study. The median cPRA at the time of failure was 12.13% (IQR = 0.00%, 83.72%) which increased to 62.76% (IQR = 4.34%, 99.18%) during the median follow-up of 27 (IQR = 18, 39) months. High HLA-DQ eplet mismatches were significantly associated with an increased risk of developing a clinically meaningful increase in cPRA (p = 0.02) and de novo DQ donor-specific antibody against the failed allograft (p = 0.02). We did not observe these associations in patients with high HLA-DR eplet mismatches. Most of the patients (88%) with a clinically meaningful increase in cPRA had both a high DQ eplet mismatch and a reduction in their immunosuppression, suggesting the association is modified by immunosuppression. The findings suggest HLA-DQ eplet mismatch analysis may serve as a useful tool to guide future clinical studies and trials which assess the management of immunosuppression in transplant failure patients who are repeat transplant candidates.